Antistatic plastic and preparation method thereof
Through the combination of polytetrafluoroethylene particles, nano-silica and homemade antistatic agents, the electrostatic problem of polytetrafluoroethylene plastics is solved, and long-term stable antistatic effect and mechanical performance improvement is achieved, which is suitable for the electronics industry.
Patent Information
- Application Number
- CN202411761548.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polytetrafluoroethylene plastics are prone to generate static charges when friction in dry air, resulting in corona discharge. The existing antistatic agents take short time to take effect and have poor compatibility with polytetrafluoroethylene plastics, making it difficult to achieve long-term effective antistatic effect.
Using a combination of polytetrafluoroethylene particles, nanosilica, silane coupling agent and homemade antistatic agent, it is prepared by mixing ultrasonic dispersion and high-speed stirring. The homemade antistatic agent is prepared through Michael addition and quaternary The ammonium salt reacts to form macromolecules with stable ammonium cations, increasing charge density and improving compatibility with polytetrafluoroethylene plastics.
It has achieved long-term stable anti-static ability and mechanical performance improvement of polytetrafluoroethylene plastics, reduced production difficulty, easy control of parameters, suitable for large-scale industrial production, and effectively prevented electrostatic accumulation and discharge in the electronics industry.
Smart Images

Figure CN119220037A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite materials, and in particular relates to an antistatic plastic and a preparation method thereof. Background Art
[0002] The resistivity of polytetrafluoroethylene plastic is usually 10 15 -10 18 Ω·cm, is an excellent insulating material with good heat resistance and corrosion resistance. However, the insulating material is prone to static charge when rubbed in dry air. When the static charge deposition causes the electric field strength on the surface to exceed the critical value, the original ions in the air will obtain enough kinetic energy to collide with other uncharged molecules, causing them to be ionized, and eventually forming partial conductivity of the air, namely corona discharge. This phenomenon is particularly harmful in the electronics industry, and therefore greatly limits the application of polytetrafluoroethylene plastics in the electronics industry.
[0003] In the prior art, antistatic agents are often added to inhibit the generation of charges and promote the leakage of charges. Among them, surface antistatic agents have a short effective time and are easily affected by the external environment, resulting in performance degradation. In addition, since polytetrafluoroethylene plastics themselves have very stable chemical properties and are extremely inert, polytetrafluoroethylene plastics have poor compatibility with polymer-type antistatic agents, making it difficult for polytetrafluoroethylene plastics to achieve long-term and effective antistatic effects. Summary of the invention
[0004] The object of the present invention is to provide an antistatic plastic and a preparation method thereof, so as to solve the problems mentioned in the above background technology.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An antistatic plastic comprises the following raw materials in parts by weight: 60-80 parts of polytetrafluoroethylene particles, 5-9 parts of nano-silicon dioxide, 1.6-3.2 parts of silane coupling agent, and 1.3-2.7 parts of antistatic agent; A method for preparing an antistatic plastic comprises the following steps: Step 1: weigh the raw materials according to the mass fractions: 60-80 parts of polytetrafluoroethylene particles, 5-9 parts of nano-silicon dioxide, 1.6-3.2 parts of silane coupling agent, and 1.3-2.7 parts of antistatic agent; Step 2: Dissolve the nano-silicon dioxide and silane coupling agent in deionized water and perform ultrasonic dispersion treatment, then filter and dry for later use; Step 3: putting polytetrafluoroethylene particles, antistatic agent, and nano-silicon dioxide treated in the second step into a mixer and stirring at high speed to prepare a pre-mixed material; Step 4: Heat and melt the prefabricated mixture obtained in the third step, stir and mix, pour into a mold, cool and process to obtain an antistatic plastic.
[0006] Furthermore, the silane coupling agent is KH-550.
[0007] Furthermore, in the second step, the temperature condition of ultrasonic dispersion is 40-70° C., and the time condition of ultrasonic dispersion is 30-45 min.
[0008] Furthermore, in the second step, the mass ratio of nano-silicon dioxide to deionized water is 1:26-35.
[0009] Furthermore, in the third step, the mixing speed condition is 300-400 r / min, and the mixing time condition is 60-80 min.
[0010] Furthermore, the temperature condition for heating and melting in the fourth step is 330-360°C.
[0011] Furthermore, the antistatic agent is prepared by the following steps: Step 1: Mix 1,1,1,3,3,3-hexafluoro-2-propylamine, 3,5-bis(trifluoromethyl)styrene and acidic alumina in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 100-120°C for 6-8h. After the reaction is completed, vacuum filter to remove the catalyst, and rotary evaporate the remaining filtrate to obtain intermediate 1; Step 2: Mix the intermediate 1, sodium hydroxide and ethanol in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, raise the system temperature to 60-75°C, add 3-chloropropylene to the three-necked flask, and continue to react for 18-24 hours. After the reaction is completed, add deionized water to the three-necked flask for washing, extract with dichloromethane, and then separate the organic layer with a separatory funnel, and rotary evaporate the organic layer to obtain the intermediate 2; Step 3: Mix the intermediate 2, 3-chloropropylene and acetonitrile in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 40-80°C for 18-24h. After the reaction is completed, rotary evaporation is performed to obtain the intermediate 3; Step 4: Mix the intermediate 3, ammonium persulfate, and the first batch of tetrasodium ethylenediaminetetraacetate in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at a temperature of 50-70°C for 1.5-2h, then add the second batch of tetrasodium ethylenediaminetetraacetate to the three-necked flask, and continue to react for 1.5-2h. After the reaction is completed, add deionized water to the three-necked flask for washing, let it stand, separate the organic layer with a separatory funnel, and the organic layer is rotary evaporated and silica gel column chromatography is performed to obtain the antistatic agent.
[0012] Furthermore, the amount ratio of 1,1,1,3,3,3-hexafluoro-2-propylamine, 3,5-bis(trifluoromethyl)styrene, and acidic alumina used in step 1 is 0.1-0.11 mol: 0.1 mol: 2.8-3.6 g.
[0013] Furthermore, the usage ratio of the intermediate 1, sodium hydroxide, ethanol and 3-chloropropylene used in step 2 is 0.08 mol: 4-4.8 g: 60-80 mL: 0.08-0.1 mol.
[0014] Furthermore, the usage ratio of the intermediate 2,3-chloropropylene and acetonitrile used in step 3 is 0.06 mol: 0.06-0.08 mol: 40-60 mL.
[0015] Furthermore, the usage ratio of intermediate 3, ammonium persulfate, the first batch of tetrasodium ethylenediaminetetraacetate, and the second batch of tetrasodium ethylenediaminetetraacetate used in step 4 is 0.05 mol: 0.114 g mol: 0.057 g: 0.076 g.
[0016] Beneficial effects of the present invention: The invention uses polytetrafluoroethylene particles, nano silicon dioxide, a silane coupling agent and a self-made antistatic agent as raw materials to prepare an antistatic plastic. The invention firstly performs ultrasonic reaction modification on nano silicon dioxide and a silane coupling agent in deionized water, then puts the polytetrafluoroethylene particles, the antistatic agent and the treated nano silicon dioxide into a mixer for high-speed stirring and mixing, and finally heats and melts the prefabricated mixture and pours it into a mold for cooling to obtain the antistatic plastic. The preparation method of the invention solves the problem of poor corona resistance of polytetrafluoroethylene plastic by blending a self-made antistatic agent, has low production difficulty, is easy to control various parameter conditions, is conducive to mass industrial production, and the nano silicon dioxide added in the preparation process can effectively fill the gap in the polytetrafluoroethylene plastic and improve the structural strength of the polytetrafluoroethylene plastic.
[0017] The present invention uses 1,1,1,3,3,3-hexafluoro-2-propylamine and 3,5-di(trifluoromethyl)styrene as raw materials, utilizes the amino group of 1,1,1,3,3,3-hexafluoro-2-propylamine and the double bond of 3,5-di(trifluoromethyl)styrene to undergo Michael addition reaction under the catalytic action of acidic aluminum oxide to obtain intermediate 1, then causes the imino group of intermediate 1 and the chlorine atom of 3-chloropropylene to undergo nucleophilic substitution reaction to obtain intermediate 2, finally causes intermediate 2 to undergo quaternary ammonium salt reaction with 3-chloropropylene to obtain intermediate 3, and finally causes the double bond of intermediate 3 to polymerize under the conditions of ammonium persulfate as an initiator and tetrasodium ethylenediaminetetraacetic acid as a complexing agent. An antistatic agent is obtained. The antistatic agent of the invention is a macromolecular polymer with a quaternary ammonium salt structure. The molecular chain carries a stable ammonium cation, which can increase the charge density of the polymer, promote the transfer of charges, and has a very obvious antistatic effect. In addition, the antistatic agent of the invention also has a large number of carbon-fluorine bonds, so it has good compatibility with a matrix tetrafluoroethylene plastic, and can be added to the tetrafluoroethylene plastic in an internal mixing manner to be effective for a long time. In addition, the antistatic agent of the invention also has a large number of benzene ring structures, which can improve the compression and tensile properties of the tetrafluoroethylene plastic, so that the prepared tetrafluoroethylene plastic can have more effective mechanical properties.
[0018] The antistatic plastic preparation method of the invention is simple, the production difficulty is low, the parameters are easy to control, and the prepared plastic has long-term stable antistatic ability and good mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The present invention will be further described below in conjunction with the accompanying drawings.
[0020] Figure 1 This is an infrared spectrum test chart of the antistatic agent prepared by the present invention. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0022] An antistatic agent comprises the following preparation steps: Step 1: 0.1 mol 1,1,1,3,3,3-hexafluoro-2-propylamine, 0.1 mol 3,5-di(trifluoromethyl)styrene and 2.8 g acidic alumina were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 100°C for 8 hours. After the reaction was completed, the catalyst acidic alumina was removed by vacuum filtration, and the obtained filtrate was rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 4 g of sodium hydroxide and 60 mL of ethanol were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, the system temperature was raised to 60°C, 0.08 mol of 3-chloropropylene was added to the three-necked flask, and the reaction was continued for 24 h. After the reaction was completed, deionized water was added to the three-necked flask, and extracted with dichloromethane. The organic layer was then separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 2; Step 3: 0.06 mol of intermediate 2, 0.06 mol of 3-chloropropylene and 40 mL of acetonitrile were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at 40°C for 24 hours. After the reaction was completed, intermediate 3 was obtained by rotary evaporation; Step 4: Mix 0.05 mol of intermediate 3, 0.114 g of ammonium persulfate and 0.057 g of tetrasodium ethylenediaminetetraacetate from the first batch in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at 50°C for 2 h. Then, add 0.076 g of tetrasodium ethylenediaminetetraacetate from the second batch to the three-necked flask and continue to react for 2 h. After the reaction is completed, add deionized water to the three-necked flask for washing, let it stand and separate the organic layer with a separatory funnel. The organic layer is rotary evaporated and subjected to silica gel column chromatography to obtain an antistatic agent. Example 2
[0023] An antistatic agent comprises the following preparation steps: Step 1: 0.105 mol 1,1,1,3,3,3-hexafluoro-2-propylamine, 0.1 mol 3,5-di(trifluoromethyl)styrene, and 3.2 g acidic alumina were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 110°C for 7 hours. After the reaction was completed, the catalyst acidic alumina was removed by vacuum filtration, and the remaining filtrate was rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 4.4 g of sodium hydroxide and 70 mL of ethanol were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, the system temperature was raised to 68°C, 0.09 mol of 3-chloropropylene was added to the three-necked flask, and the reaction was continued for 21 hours. After the reaction was completed, deionized water was added to the three-necked flask, and extracted with dichloromethane, and then the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 2; Step 3: 0.06 mol of intermediate 2, 0.07 mol of 3-chloropropylene and 50 mL of acetonitrile were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at 60°C for 21 hours. After the reaction was completed, intermediate 3 was obtained by rotary evaporation; Step 4: Mix 0.05 mol of intermediate 3, 0.114 g of ammonium persulfate and 0.057 g of tetrasodium ethylenediaminetetraacetate from the first batch in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at 60°C for 1.8 h. Then, add 0.076 g of tetrasodium ethylenediaminetetraacetate from the second batch to the three-necked flask and continue to react for 1.8 h. After the reaction is completed, add deionized water to the three-necked flask for washing, let it stand and separate the organic layer with a separatory funnel. The organic layer is rotary evaporated and subjected to silica gel column chromatography to obtain an antistatic agent. Example 3
[0024] An antistatic agent comprises the following preparation steps: Step 1: 0.11 mol 1,1,1,3,3,3-hexafluoro-2-propylamine, 0.1 mol 3,5-di(trifluoromethyl)styrene, and 3.6 g acidic alumina were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 120°C for 6 hours. After the reaction was completed, the catalyst acidic alumina was removed by vacuum filtration, and the remaining filtrate was rotary evaporated to obtain intermediate 1; Step 2: 0.08 mol of intermediate 1, 4.8 g of sodium hydroxide and 80 mL of ethanol were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, the system temperature was raised to 75°C, 0.1 mol of 3-chloropropylene was added to the three-necked flask, and the reaction was continued for 18 h. After the reaction was completed, deionized water was added to the three-necked flask for washing, and extracted with dichloromethane, and then the organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 2; Step 3: 0.06 mol of intermediate 2, 0.08 mol of 3-chloropropylene and 60 mL of acetonitrile were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at 80°C for 18 h. After the reaction was completed, intermediate 3 was obtained by rotary evaporation; Step 4: Mix 0.05 mol of intermediate 3, 0.114 g of ammonium persulfate and 0.057 g of tetrasodium ethylenediaminetetraacetate from the first batch in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and react at 70°C for 1.5 h. Then, add 0.076 g of tetrasodium ethylenediaminetetraacetate from the second batch to the three-necked flask and continue to react for 1.5 h. After the reaction is completed, add deionized water to the three-necked flask for washing, let it stand and separate the organic layer with a separatory funnel. The organic layer is rotary evaporated and subjected to silica gel column chromatography to obtain an antistatic agent.
[0025] Analysis example 1 The antistatic agent prepared in Example 1 was analyzed by infrared spectroscopy using a Nicolet 6700 Fourier transform infrared spectrometer produced by Thermo Corporation of the United States. Figure 1 As shown in the infrared spectrum of the antistatic agent, The carbon-fluorine bond absorption peak appears. The quaternary ammonium structure absorption peak appears. The benzene ring absorption peak appears. The carbon-nitrogen bond absorption peak appears. Example 4
[0026] An antistatic plastic comprises the following raw materials in parts by weight: 60 parts of polytetrafluoroethylene particles, 5 parts of nano-silicon dioxide, 1.6 parts of KH-550 silane coupling agent, and 1.3 parts of the antistatic agent obtained in Example 1; A method for preparing an antistatic plastic comprises the following steps: Step 1: weigh the raw materials according to their mass fractions: 60 parts of polytetrafluoroethylene particles, 5 parts of nano-silicon dioxide, 1.6 parts of KH-550 silane coupling agent, and 1.3 parts of the antistatic agent obtained in Example 1; Step 2: Dissolve the nano-silica and KH-550 silane coupling agent in deionized water and perform ultrasonic dispersion treatment for 45 minutes at a temperature of 40°C, then filter and dry for later use, wherein the mass ratio of nano-silica, KH-550 silane coupling agent and deionized water is 5:1.6:130; Step 3: Put the polytetrafluoroethylene particles, the antistatic agent obtained in Example 1, and the nano-silicon dioxide treated in the second step into a mixer and stir and mix them at a high speed of 300 r / min for 80 minutes to prepare a pre-mixed material; Step 4: Heat the prefabricated mixture obtained in the third step to 330° C., stir and mix, pour into a mold, cool and obtain an antistatic plastic. Example 5
[0027] An antistatic plastic comprises the following raw materials in parts by weight: 60 parts of polytetrafluoroethylene particles, 5 parts of nano-silicon dioxide, 3.2 parts of KH-550 silane coupling agent, and 2.7 parts of the antistatic agent obtained in Example 2; A method for preparing an antistatic plastic comprises the following steps: Step 1: weigh 60 parts of polytetrafluoroethylene particles, 5 parts of nano-silicon dioxide, 3.2 parts of KH-550 silane coupling agent, and 2.7 parts of the antistatic agent obtained in Example 2 according to their mass fractions; Step 2: Dissolve the nano-silica and KH-550 silane coupling agent in deionized water and perform ultrasonic dispersion treatment at 60°C for 40 minutes, then filter and dry for later use, wherein the mass ratio of nano-silica, KH-550 silane coupling agent and deionized water is 7:2.4:205; Step 3: Put the polytetrafluoroethylene particles, the antistatic agent obtained in Example 2, and the nano-silicon dioxide treated in the second step into a mixer and stir and mix at a high speed of 350 r / min for 70 minutes to prepare a pre-mixed material; Step 4: Heat the prefabricated mixture obtained in the third step to 340°C to melt, stir and mix, pour into a mold, cool and obtain an antistatic plastic. Example 6
[0028] An antistatic plastic comprises the following raw materials in parts by weight: 80 parts of polytetrafluoroethylene particles, 9 parts of nano-silicon dioxide, 1.6 parts of KH-550 silane coupling agent, and 1.3 parts of the antistatic agent obtained in Example 3; A method for preparing an antistatic plastic comprises the following steps: Step 1: weigh 80 parts of polytetrafluoroethylene particles, 9 parts of nano-silicon dioxide, 1.6 parts of KH-550 silane coupling agent, and 1.3 parts of the antistatic agent obtained in Example 3 according to their mass fractions; Step 2: Dissolve the nano-silica and KH-550 silane coupling agent in deionized water and perform ultrasonic dispersion treatment for 30 minutes at 70°C, then filter and dry for later use, wherein the mass ratio of nano-silica, KH-550 silane coupling agent and deionized water is 9:3.2:315; Step 3: Put the polytetrafluoroethylene particles, the antistatic agent obtained in Example 3, and the nano-silicon dioxide treated in the second step into a mixer and stir and mix them at a high speed of 400 r / min for 60 minutes to prepare a pre-mixed material; Step 4: Heat the prefabricated mixture obtained in the third step to 360°C to melt, stir and mix, pour into a mold, cool and obtain an antistatic plastic.
[0029] Comparative Example 1 An antistatic plastic comprises the following raw materials in parts by weight: 80 parts of polytetrafluoroethylene; A method for preparing an antistatic plastic comprises the following steps: 80 parts by mass of polytetrafluoroethylene particles are heated to 360° C., melted, stirred and mixed, poured into a mold, and cooled to obtain an antistatic plastic.
[0030] Comparative Example 2 An antistatic plastic comprises the following raw materials in parts by weight: 80 parts of polytetrafluoroethylene particles and 9 parts of nano silicon dioxide; A method for preparing an antistatic plastic comprises the following steps: Step 1: weigh 80 parts of polytetrafluoroethylene particles and 9 parts of nano-silicon dioxide according to their mass fractions; Step 2: Put the polytetrafluoroethylene particles and nano-silicon dioxide into a mixer and stir and mix them at a high speed of 400 r / min for 60 minutes to prepare a pre-mixed material; Step 3: Heat the prefabricated mixture obtained in the second step to 360°C, stir and mix, pour into a mold, cool and obtain an antistatic plastic.
[0031] Comparative Example 3 An antistatic plastic comprises the following raw materials in parts by weight: 80 parts of polytetrafluoroethylene particles, 9 parts of nano-silicon dioxide, and 1.6 parts of KH-550 silane coupling agent; A method for preparing an antistatic plastic comprises the following steps: Step 1: weigh 80 parts of polytetrafluoroethylene particles, 9 parts of nano-silicon dioxide, and 1.6 parts of KH-550 silane coupling agent according to their mass fractions; Step 2: Dissolve the nano-silica and KH-550 silane coupling agent in deionized water and perform ultrasonic dispersion treatment at 70°C for 30 minutes, then filter and dry for later use; Step 3: Put the polytetrafluoroethylene particles and the nano-silicon dioxide treated in the second step into a mixer and stir and mix them at a high speed of 400 r / min for 60 minutes to prepare a pre-mixed material; Step 4: Heat the prefabricated mixture obtained in the third step to 360°C to melt, stir and mix, pour into a mold, cool and obtain an antistatic plastic.
[0032] Comparative Example 4 This comparative example is the polytetrafluoroethylene accessories sold by Xingtai Lichuang Machinery Parts Co., Ltd.
[0033] The antistatic plastics in Examples 4-6 and Comparative Examples 1-3 and the commercially available polytetrafluoroethylene accessories in Comparative Example 4 were tested for surface resistivity at room temperature using an insulation resistance tester, and the friction resistance test was performed in accordance with GB / T3960-2016. The test results are shown in Table 1: Table 1 ; It can be seen from Table 1 that the resistivity of the antistatic plastic prepared by the preparation method of the present invention in Examples 4-6 is much lower than the resistance of the commercially available polytetrafluoroethylene accessories and is less than 10 13Ω·cm, so the antistatic plastic of the present invention can effectively prevent the accumulation and discharge of static electricity, and has excellent antistatic ability. In Comparative Examples 1-3, the effects of other raw materials of the present invention on the properties of the antistatic plastic are demonstrated in turn through control experiments. The nano silicon dioxide in the raw materials can enhance the friction resistance of the antistatic plastic. The silane coupling agent can further enhance the binding force between the nano silicon dioxide and the antistatic plastic, and further enhance the friction resistance of the antistatic plastic. In addition, the nano silicon dioxide and the silane coupling agent have no obvious effect on the antistatic property of the plastic. In summary, the antistatic plastic prepared by the preparation method of the present invention has good antistatic ability and can be widely used in the fields of electrical housings, electronic components, and electronic packaging.
[0034] The above is a detailed introduction to an antistatic plastic and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and core ideas of the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combination method. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention can be used in combination with each other in any way. The fact that these combinations are not exhaustively described in this specification is only for the purpose of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. An antistatic plastic, characterized in that: The invention comprises the following raw materials in parts by weight: 60-80 parts of polytetrafluoroethylene particles, 5-9 parts of nano-silicon dioxide, 1.6-3.2 parts of silane coupling agent, and 1.3-2.7 parts of antistatic agent; Wherein, the antistatic agent is prepared by the following steps: Step 1: Mix 1,1,1,3,3,3-hexafluoro-2-propylamine, 3,5-di(trifluoromethyl)styrene and acidic alumina in a container, stir evenly, and react at 100-120°C for 6-8h to obtain intermediate 1; Step 2: Mix the intermediate 1, sodium hydroxide and ethanol in a container, stir evenly, raise the system temperature to 60-75°C, then add 3-chloropropylene to the three-necked flask, and continue the reaction for 18-24 hours to obtain the intermediate 2; Step 3: Mix the intermediate 2, 3-chloropropylene and acetonitrile in a container, stir evenly, and react at a temperature of 40-80° C. for 18-24 hours to obtain the intermediate 3; Step 4: Mix the intermediate 3, ammonium persulfate, and the first batch of tetrasodium ethylenediaminetetraacetate in a container, stir evenly, and react at a temperature of 50-70° C. for 1.5-2 hours, then add the second batch of tetrasodium ethylenediaminetetraacetate to the container, and continue to react for 1.5-2 hours to obtain the antistatic agent.
2. The antistatic plastic according to claim 1, characterized in that: The amount ratio of 1,1,1,3,3,3-hexafluoro-2-propylamine, 3,5-bis(trifluoromethyl)styrene and acidic alumina used in step 1 is 0.1-0.11 mol: 0.1 mol: 2.8-3.6 g.
3. The antistatic plastic according to claim 1, characterized in that: The usage ratio of intermediate 1, sodium hydroxide, ethanol and 3-chloropropylene used in step 2 is 0.08 mol: 4-4.8 g: 60-80 mL: 0.08-0.1 mol.
4. The antistatic plastic according to claim 1, characterized in that: The usage ratio of the intermediate 2,3-chloropropylene and acetonitrile used in step 3 is 0.06 mol: 0.06-0.08 mol: 40-60 mL.
5. The antistatic plastic according to claim 1, characterized in that: The amount ratio of intermediate 3, ammonium persulfate, the first batch of tetrasodium ethylenediaminetetraacetate, and the second batch of tetrasodium ethylenediaminetetraacetate used in step 4 is 0.05 mol: 0.114 g mol: 0.057 g: 0.076 g.
6. A method for preparing an antistatic plastic, characterized in that: The following steps are involved: Step 1: weigh the raw materials according to the mass fractions: 60-80 parts of polytetrafluoroethylene particles, 5-9 parts of nano-silicon dioxide, 1.6-3.2 parts of silane coupling agent, and 1.3-2.7 parts of antistatic agent; Step 2: dissolving the nano-silicon dioxide and the silane coupling agent in deionized water and performing ultrasonic dispersion treatment, and then filtering and drying to obtain the treated nano-silicon dioxide; Step 3: putting polytetrafluoroethylene particles, antistatic agent, and nano-silicon dioxide treated in the second step into a mixer and stirring at high speed to prepare a pre-mixed material; Step 4: Heat and melt the prefabricated mixture obtained in the third step, stir and mix, pour into a mold, cool and process to obtain an antistatic plastic.
7. The method for preparing an antistatic plastic according to claim 6, characterized in that: The silane coupling agent is KH-550, wherein the mass ratio of nano silicon dioxide, the silane coupling agent and deionized water is 5-9:1.6-3.2:130-315.
8. The method for preparing an antistatic plastic according to claim 6, characterized in that: In the second step, the temperature condition of ultrasonic dispersion is 40-70°C, and the time condition of ultrasonic dispersion is 30-45min.
9. The method for preparing an antistatic plastic according to claim 6, characterized in that: In the third step, the mixing speed condition is 300-400 r / min, and the mixing time condition is 60-80 min.
10. The method for preparing an antistatic plastic according to claim 6, characterized in that: The temperature condition for heating and melting in the fourth step is 330-360°C.
Citation Information
Patent Citations
Polytetrafluoroethylene product and preparation method thereof
CN106243591A
Antistatic flexible Teflon film and production process thereof
CN107022159A
Antistatic flame-retardant cable sheath material
CN107383811A
Antistatic packaging plastic film
CN114891291A
